Adoption of Software Testing in Internet of Things: A Systematic Literature Mapping - Cortés, Mariela; Saraiva, Raphael; Souza, Marcia; Mello, Patricia; Soares, Pamella (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2019)
The Internet of Things (IoT) is a paradigm based on the interaction between intelligent devices (things) and physical and/or virtual resources through the Internet. Thus, applications in this domain may become more prone to failures. In this scenario, evaluating the quality of applications through software testing can be considered critical and challenging. The focus of this work is to obtain a comprehensive understanding of the adoption of Software Testing in the context of IoT, identifying gaps in existing approaches, and providing new directions for research in the area. To achieve this goal, a systematic mapping covering research papers published in journals and conferences was carried out, accessing four relevant electronic databases. As a result, a total of 79 studies were selected and analyzed in order to evaluate quantitatively and qualitatively, the effective adoption of software testing in the projects.